Inventory of attitudes toward seeking mental health services: psychometric properties among adolescents - Brás, Marta (2022)
Mental health is an essential element of wellness; however, some populations are more vulnerable to mental health problems. Suicide is the second-highest cause of death in young people and help-seeking unwillingness is a significant obstacle to mental health interventions. Young people are especially reluctant to seek help and negative attitudes stand out as help-seeking barriers, highlighting the importance of evaluating these constructs. The Inventory of Attitudes toward Seeking Mental Health Services (IASMHS) is a measure that evaluates help-seeking attitudes; nevertheless, it lacks applicability in Portuguese youth. This study aims to explore the psychometric characteristics of the IASMHS in 750 Portuguese adolescents (52.3% female, Mage = 14.67), through exploratory and confirmatory factor analysis, and reliability and validity analyses. Results suggest that a three-factor structure was adequate, those factors being help-seeking propensity, indifference to stigma, and psychological openness. The IASMHS was shortened to 20 items and revealed satisfactory properties regarding internal consistency, convergent/discriminant validity, and temporal stability. These findings validate the IASMHS as an adequate tool in the assessment of young people’s help-seeking attitudes.